Venous malformations in children - a literature review - Dobek, Adam; Korol, Filip; Symulewicz, Michał; Edyko, Krzysztof; Jachowicz, Krzysztof; Minkner, Mikołaj; Bieńkowski, Borys; Feja, Krzysztof; Marchewka, Urszula; Łuczak, Ewa (Journal of Education, Health and Sport, 2023)
Introduction: Venous malformations are congenital, the most occurring subtype of vascular malformations. They are characterized by slow flow, tortuosity and lack of macular layer within the vessel. Venous malformations can be highly problematic to diagnose and treat, thus differentiation the venous malformations with other diseases in pediatric population is important. Aim of the study: The aim of the study is to summarize the available knowledge about venous malformation in pediatric population. The options in diagnosis, treatment and potential new methods were summarized and described. Materials and methods The literature available in the PubMed database was reviewed using the following keywords: “Vascular malformations”, “Venous Malformations”, “Venous malformations treatment, “Children”. Conclusions: Venous malformations are an important problem in pediatric population, as a seldom affliction they can be easily misdiagnosed as other diseases and treated inadequately. Widening of awareness of venous malformations and possible methods of diagnosing and treating them is very important to raise quality of health care in children.